The educational structure of the population in the city of Maribor - Horvat, Uroš (Journal for Geography, 2017)
In the introduction, the author analyzes the educational structure of the population (by educational attainment level) in the larger Slovene towns, and compares it with the structure in Maribor, which is the second largest university town in Slovenia. He finds that Maribor is among the cities with the highest percentage of population with a tertiary education in Slovenia, but the population with a secondary education is still above the average, which is a result of the intensive development of industrial activity in the past decades. Continuing, he analyzes the situation in individual parts of the city of Maribor, and finds important differences between the individual parts of the city. The area on the left bank of the Drava River shows a higher proportion of population with tertiary education, while the areas on the right bank, especially the areas with older buildings constructed in the fifties, sixties, and seventies, and the areas around the older industrial zones show a higher proportion of population with primary education.
Keywords: educational structure; tertiary education; Maribor; Slovenia